Jane Franklin (ed.), The Politics of Risk Society, Oxford, Polity Press, 1998 - Lezama, José Luis (Estudios Demográficos y Urbanos, 1998)
Jane Franklin (ed.), The Politics of Risk Society, Oxford, Polity Press, 1998.